Flow visualisation around spinning and non-spinning soccer balls using the lattice Boltzmann method - Asai, T.; Hong, S.; Kimachi, K.; Abe, K.; Kai, H.; Nakamura, A. (Proceedings, 2018)
The drag and lift of footballs have been mainly measured by wind tunnel tests. In the present study, computational fluid dynamics (CFD) and the lattice Boltzmann method were used to visualise the wakes of spinning and non-spinning footballs and analyse the dynamics of the observed vortex structures. The dominant vortex structures in the wakes of the footballs were determined to be large-scale counter-rotating vortex pairs. The fluctuation of the vortex pair for the spinning football was also estimated to be smaller and more stable than that for the non-spinning football. Although the presence of an unstable, large-scale counter-rotating vortex pair in the wake of a non-spinning ball has been previously observed in wind tunnel tests, the present study particularly found that the dominant vortex structure of a spinning ball was a stable, large-scale counter-rotating vortex pair.